Consumption of complement in a 26-year-old woman with severe thrombotic thrombocytopenia after ChAdOx1 nCov-19 vaccination. Issue 124 (November 2021) - Cugno, Massimo; Macor, Paolo; Giordano, Mara; Manfredi, Marcello; Griffini, Samantha; Grovetti, Elena; De Maso, Luca; Mellone, Simona; Valenti, Luca; Prati, Daniele; Bonato, Sara; Comi, Giacomo; et al.
Abstract: Extremely rare reactions characterized by thrombosis and thrombocytopenia have been described in subjects that received ChAdOx1 nCoV-19 vaccination 5–16 days earlier. Although patients with vaccine-induced thrombotic thrombocytopenia (VITT) have high levels of antibodies to platelet factor 4 (PF4)–polyanion complexes, the exact mechanism of the development of thrombosis is still unknown. Here we reported serum studies as well as proteomics and genomics analyses demonstrating a massive complement activation potentially linked to the presence of anti-PF4 antibodies in a patient with severe VITT. At admission, complement activity of the classical and lectin pathways were absent (0% for both) with normal levels of the alternative pathway (73%) in association with elevated levels of the complement activation marker sC5b-9 (630 ng/mL [n.v. 139–462 ng/mL]) and anti-PF4 IgG (1.918 OD [n.v. 0.136–0.300 OD]). The immunoblotting analysis of C2 showed the complete disappearance of its normal band at 110 kDa. Intravenous immunoglobulin treatment allowed to recover complement activity of the classical pathway (91%) and lectin pathway (115%), to reduce levels of sC5b-9 (135 ng/mL) and anti-PF4 IgG (0.681 OD) and to normalize the C2 pattern at immunoblotting. Proteomics and genomics analyses in addition to serum studies showed that the absence of complement activity during VITT was not linked to alterations of the C2 gene but rather to a strong complement activation leading to C2 consumption. Our data in a single patient suggest monitoring complement parameters in other VITT patients considering also the possibility to target complement activation with specific drugs. Graphical abstract: Image 1 Highlights: Complement consumption was seen in a case of vaccine induced thrombotic thrombocytopenia. Proteomics and genomics studies showed that complement consumption was due to its activation. Intravenous immunoglobulin treatment allowed to recover complement activity.